STRATEGI OPTIMALISASI PEMBELAJARAN PRAKTIK IPS DI SEKOLAH DASAR: PEMANFAATAN MEDIA LINGKUNGAN SEBAGAI SOLUSI KETERBATASAN SARANA PRASARANA - Azzahra Salmanabila Parsha; Yoga Pratama; Shanata Pratiwi; Aulia Yunita Rosanti; Latifa Ruliandari; Febri Nur Salamah; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social studies learning in elementary schools often experiences obstacles in the implementation of practices due to lack of student activity and limited facilities and infrastructure. This study examines strategies that teachers can apply to optimize social studies learning practices by utilizing environmental media around the school. The results of the literature review show that the use of environmental media creatively and in a structured manner can increase student involvement and overcome limited facilities and infrastructure. A contextual approach using local resources has proven effective in creating meaningful learning experiences and improving understanding of social studies concepts in elementary school students